Trademark dilution: comparing the effects of blurring and tarnishment cases over brand equity - Macías, Washington (2015)
Trademark dilution is, in a general sense, a reduction in brand equity due to the unauthorized use of the trademark by third parties (junior brands). Although there are two types of dilution, blurring and tarnishment, existing academic empirical evidence only relates to blurring cases, showing its damage to some variables related to brand associations in consumers’ minds. Literature also shows the moderating role of the similarity between junior brands, but this evidence is not complete unless presumable tarnishment cases are analyzed. This paper compares the effect of two types of junior brands over strength of associations and brand equity of famous trademarks. An experimental approach was applied with a sample of 372 undergraduate students, users of two famous convenience brands. Junior brands use identical or similar famous brand names in different product categories, offering a continuous of similarity levels, so the moderating effect of this variable is analyzed. Results show that: (i) dependent variables are reinforced when junior brands are perceived as very similar, and diluted above some degree of dissimilarity; (ii) dilution increases the more dissimilar the junior brand. However, although they have a high degree of dissimilarity, cases of presumable tarnishment, might not always produce dilution. Besides, they suggest that the effect induced by similarity is not linear. These findings are discussed through the lenses of marketing and psychology theories. The study represents a contribution to the field, providing evidence not only from blurring cases, but also from supposed tarnishing imitators, comparing their effects and showing the limited moderating effect of similarity. The boundary conditions of similarity effects in trademark dilution literature have not been discussed previously. Finally, main implications for managers are highlighted, given the negative effects that trademark dilution may entail at firm level.